2016
DOI: 10.1007/s10681-016-1771-6
|View full text |Cite
|
Sign up to set email alerts
|

QTLs for oil yield components in an elite oil palm (Elaeis guineensis) cross

Abstract: Increased modern farming of superior types of the oil palm, Elaeis guineensis Jacq., which has naturally efficient oil biosynthesis, has made it the world's foremost edible oil crop. Breeding improvement is, however, circumscribed by time and costs associated with the tree's long reproductive cycle, large size and 10-15 years of field testing. Markerassisted breeding has considerable potential for improving this crop. Towards this, quantitative trait loci (QTL) linked to oil yield component traits were mapped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Further, Billotte et al [15] used a multi-parent linkage map elaborated with 251 SSRs and reported QTLs associated with bunch traits. Similar approaches have enabled the identification of 164 QTLs associated with 21 oil yield components using SSR, AFLP, and RFLP markers [16].…”
Section: Introductionmentioning
confidence: 99%
“…Further, Billotte et al [15] used a multi-parent linkage map elaborated with 251 SSRs and reported QTLs associated with bunch traits. Similar approaches have enabled the identification of 164 QTLs associated with 21 oil yield components using SSR, AFLP, and RFLP markers [16].…”
Section: Introductionmentioning
confidence: 99%
“…Genetically speaking, oil accumulation in plant tissues is a complex quantitative trait that involves numerous genes. Efforts to increase oil yields in commercially valuable crops, such as E. guineensis and oilseeds like soybean, require the identification of the specific genes that regulate this highly desirable agronomic trait so that breeders can focus on variation involving those key genes [52] in a similar manner to efforts to manipulate the acyl quality of the oil [53]. It is becoming increasingly apparent that DGAT activity is pivotal to increasing…”
mentioning
confidence: 99%
“…GWAS, QTL and association mapping studies have been increasingly reported for oil palm breeding, particularly for oil content [115][116][117][118][119][120]. Bai et al [116] showed that by combining QTLs with beneficial genotypes, the resulting average oil content in fruit bunches was higher.…”
Section: Oil Palm Omics Research Related To Yieldmentioning
confidence: 99%
“…This platform was particularly useful for developing early trait prediction methods to shorten the oil palm breeding cycle and was used to identify QTL loci for important oil content traits [115]. Informative QTLs linked to oil yield component traits were also mapped in a high-yield population [118]. The authors highlighted the significance of cumulative effects of quantitative trait allele analysis for each trait contributing to oil yield components.…”
Section: Oil Palm Omics Research Related To Yieldmentioning
confidence: 99%